There And Back Again: Women's Marginal Commuting Costs - Isabel Stockton; Annette Bergemann; Stephan Brunow (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We use a partial-equilibrium model of job search with non-wage job attributes to estimate female workers' marginal willingness to pay to reduce commuting distance in Germany. This issue not only has implications for congestion policy, spatial planning and transport infrastructure provision, but is also relevant to our understanding of gender differences in labour market biographies in a more general sense. Gender differences in willingness to pay for job attributes could contribute significantly to observed disparities in a number of labour market behaviours and outcomes, such as participation, labour supply, wages and job mobility. Our analysis makes particular reference to heterogeneity by regional structure and local labour market conditions, and outlines ways of incorporating other types of heterogeneity into the analysis. Using a Cox model on a large administrative dataset, we find a marginal willingness to pay of e0.15 of women workers to reduce commuting distance by one kilometre. Keywords: Commuting, marginal willingness to pay for job attributes, on-the-job search, Cox relative risk model, partial likelihood estimation, gender and parenthood in job search models, heterogeneity in job mobility.
Keywords: C41; J61; J16; 330